2013
DOI: 10.4236/oje.2013.35040
|View full text |Cite
|
Sign up to set email alerts
|

Plants used in traditional beekeeping in Burkina Faso

Abstract: Beekeeping is one of the recommended approaches in the implementation of poverty alleviation programs in rural areas of Burkina Faso. However, plants that are important in beekeeping have not been identified. The use of parts and organs of plants by beekeepers and their methods of harvesting remain unknown. These limit the conservation efforts of these important plants and affect beekeeping development. The study was carried out in the south-central, eastcentral regions and in Comoé and Boucle of Mouhoun regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
6
0
1
Order By: Relevance
“…Hive products reflect in quantity and quality the nature of the plants foraged [1] [4] [5]. Beekeeping is an effective means to generate monetary incomes that support the livelihood of rural communities [6]. Numerous studies have demonstrated the economic value of honeybees to the agricultural industry of the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hive products reflect in quantity and quality the nature of the plants foraged [1] [4] [5]. Beekeeping is an effective means to generate monetary incomes that support the livelihood of rural communities [6]. Numerous studies have demonstrated the economic value of honeybees to the agricultural industry of the world.…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, especially areas in south of Sahara, this phenomenon is not fully known because of the lack of scientific studies [6]. Therefore the study of melliferous plants is of great interest.…”
Section: Introductionmentioning
confidence: 99%
“…All honey samples analysed contain minor pollens, 90% of them contain the important minor pollen, 50% secondary pollen and 60% dominant pollens. [43]) and Schweitzer [44], the identification of a pollen grain even isolated in honey can have very important consequences for the knowledge of it geographical origin. Syzygium guineense pollens are present in all honey samples analyzed.…”
Section: Frequency Of Beeplantsmentioning
confidence: 99%
“…Dans les pays pauvres comme le Bénin, l'apiculture est une vieille pratique du système de production agricole. Elle constitue l'une des rares activités qui nécessite peu d'investissements et qui fournit des revenus substantiels, en même temps qu'elle contribue à la protection de l'environnement (Schweitzer et al, 2013 ;Amakpe et al, 2015). Pour Fosto et al (2014), le meilleur moyen d'accroître la production et la productivité de l'apiculture est d'en avoir une bonne connaissance.…”
Section: Introductionunclassified